Intermonitor Variability of GT3X Accelerometer - Santos-Lozano, A.; Torres-Luque, G.; Marín, P. J.; Ruiz, J. R.; Lucia, A.; Garatachea, N. (International Journal of Sports Medicine, 2012)
The main purpose of this study was to assess the inter-monitor reliability of the tri-axial GT3X Actigraph accelerometer over a range of physical activities (PA). This device collects motion data on each of the vertical (Y), horizontal right-left (X), and horizontal front-back (Z) axes and also calculates the vector summed value √X2+Y2+Z2 known as ‘vector magnitude’ (VM). 8 GT3X accelerometers were worn at the same time by the same participant. Accelerometers were placed back-to-front, all facing forward and in sets of 4 securely taped together, attached to a belt and allocating each block above either left or right hip at waist level. Inter-monitor reliability was assessed during 6 conditions: rest, walking (4 and 6 km·h − 1), running (8 and 10 km·h − 1) and repeated sit-to-stand (40 times·min − 1). The intra-class correlation coefficients were high for X, Y and Z axes (i. e., all ≥0.925) and for VM (≥0.946). In conclusion, we found good inter-instrument reliability of the GT3X accelerometer across all planes, yet our results also suggest that the X and Z axes do not provide further benefits over the ‘traditional’ Y-axis to assess the movement in typical PA.
Keywords: physical activity; activity assessment; accelerometry; motion sensor